High conversion of CO2 into cyclic carbonates under solvent free and ambient pressure conditions by a Fe-cyanide complex. (24th October 2019) - Jiang, Pengbo; Ma, Lei; Wang, Kaizhi; Lan, Kai; Zhan, Zhenzhen; Iqbal, Anam; Niu, Fang; Li, Rong
Abstract : Methods of converting carbon dioxide into valuable chemicals are of great demand but their development is still challenging. Abstract : Methods of converting carbon dioxide into valuable chemicals are of great demand but their development is still challenging. Herein, we developed an efficient, green and facile synthetic method for the preparation of a Fe-cyanide complex. The target catalyst showed high catalytic activity for the cyclic reaction of carbon dioxide and epoxide under solvent free conditions and ambient pressure. Meanwhile, the effects of morphology of different catalysts on their catalytic activities were also investigated by the kinetic and thermodynamic studies. In addition, the catalyst could be recycled and reused for at least five successive cycles without significant decrease in the catalytic activity. This target catalyst thus represents one of the efficient and recyclable systems reported for the cyclic reaction in industry.